The Correlation between Student’s Perception and Comprehension Achievement of the English Language Derivational Morphology - Bunau, Eusabinus (Lingua Cultura, 2022)
The research investigated the correlation between the perception and achievement of the students of English language derivational morphology comprehension. The perception was what was claimed, and the achievement was what was gained. There were primary and secondary data in the research. The primary data were collected by survey, and the secondary data were taken from the mid-test score record documented in the Academic Information System. The survey was implemented by distributing 18 questionnaire statements to 62 respondent students enrolling in English Morphology class. The non-parametric data resulted from the Likert Scale of 1 to 4 options. The perception was interpreted using the index percentage equation, and the interval of percentage was 25. Moreover, the achievement was calculated using the mean score equation. The Pearson Product Moment formula was applied to compute the correlation between perception and achievement. It is revealed that the students’ perception index on the English language derivational morphology is 52,53%, falling into the criteria of 50,01%-75,00% with the category of ‘I get it’. Furthermore, the mean score of student achievement is 76,45 and is categorized as ‘good’, placing in the range of 70,00-79,99. The research concludes that the null hypothesis is accepted, and the perception does not correlate linearly with the achievement of the comprehension of the English language derivational morphology. The correlation coefficient is -0,04365, and the category of the correlation is negligible. Despite the correlation and its category, this research infers that the perception is understandable, and comprehension is achievable.